Associations between syndesmophytes and facet joint ankylosis in radiographic axial spondyloarthritis patients on low-dose CT over 2 years. (18th March 2022) - Stal, Rosalinde; Sepriano, Alexandre; van Gaalen, Floris Alexander; Baraliakos, Xenofon; van den Berg, Rosaline; Reijnierse, Monique; Braun, Juergen; Landewé, Robert B M; van der Heijde, Désirée
Abstract: Objectives: In radiographic axial spondyloarthritis (r-axSpA), spinal damage manifests as syndesmophytes and facet joint ankylosis (FJA). We evaluated whether the presence of one lesion increased the risk of the other lesion. Methods: Patients with r-axSpA underwent low-dose CT (ldCT) and MRI of the whole spine at baseline and 2 years. On ldCT, vertebrae were scored for presence and size of syndesmophytes; facet joints were assessed for ankylosis. MR images were assessed for inflammation. Two hypotheses were tested: (i) presence of FJA is associated with new syndesmophyte(s) on the same vertebral unit (VU) 2 years later, and (ii) presence of bridging syndesmophyte(s) is associated with new FJA on the same VU 2 years later. Two generalized estimating equations models were tested per hypothesis using increase of FJA/syndesmophytes (model A) or presence of FJA/syndesmophytes (model B) as outcome, adjusted for inflammation at baseline. Secondary analyses tested the hypotheses with outcomes on adjacent VUs and dose–response effects. Results: Fifty-one patients were included (mean age 49, 84% male, 82% HLA-B27 + ). Baseline bridging syndesmophytes occurred more often (range: 10–60% per VU) than FJA (range: 8–36%). Odds ratios (ORs) (95% CI) for presence of bridging syndesmophytes on development of FJA were 3.55 (2.03, 6.21) for model A and 3.30 (2.14, 5.09) for model B. ORs for presence of baseline FJA on new syndesmophytes were 1.87 (1.20, 2.92) for model A and 1.69 (0.88, 3.22) for model B. Secondary analyses yielded positive ORs for both hypotheses. Conclusions: Bone formation in vertebrae and in facet joints influence each other's occurrence, with the effect of syndesmophytes being larger than that of FJA.